Adult height, body mass index and time of menarche of girls with idiopathic central precocious puberty after gonadotropin-releasing hormone analogue treatment - Preamrudee Poomthavorn (2018)
Background.?Long-term outcome data of central precocious puberty (CPP) girls treated with gonadotropin-releasing hormone analogue (GnRHa) are conflicting. Aim.?To assess long-term outcome of girls with idiopathic CPP (iCPP) treated with GnRHa Methods.?We compared adult height (AH), body mass index (BMI) and time of menarche in GnRHa-treated (n = 47) and untreated (n = 11) girls with iCPP. Results.?There were no differences in age, bone age, height, weight and BMI z-scores, predicted adult height (PAH) at the time of diagnosis and target height between the two groups. Mean (SD) age of GnRHa-treated girls was 8.5 (1.0) years at the start of treatment. Mean (SD) AH of the treated group was greater [158.6 (5.2) vs. 154.8 (5.6) cm], p < 0.05. AH gain over pre-treatment PAH in the treated group was 4.7 cm. BMI z-score of treated girls was 1.26 (0.95) before the treatment initiated and returned to normal [0.16 (1.0)] at the time of AH reached. Menstruation occurred at 0.9 (0.5) years following GnRHa discontinuation with regular pattern. Conclusions.?Long-term GnRHa therapy has a modest beneficial effect on adult height gain in girls with iCPP. No detrimental effects on increasing BMI and hypothalamicpituitarygonadal axis reactivation are demonstrated. © 2010 Informa UK, Ltd.